Case Study on Sustainability of Rural Sanitation Marketing in Vietname - Sijbesma, Christine (World Bank, Washington, DC, 2014)
This case study of the sustainability of rural sanitation marketing is part of a wider activity entitled 'Total Sanitation and Sanitation Marketing (TSSM): new approaches to Stimulate and Scale up Sanitation Demand and Supply Project,' also known as the Global Scaling up Sanitation Project. The long-term vision for this effort is to help a number of developing countries meet the basic sanitation needs of the rural poor who do not currently have access to safe and hygienic sanitation. TSSM tests proven and promising approaches to create demand for sanitation and improve the supply of sanitation-related products and services to increase household access to safe and sustainable sanitation; create open-defecation free communities; and promote improved hygiene practices. Though not one of the TSSM focus countries, Vietnam is one of the countries where a piloted approach to enhance and meet rural sanitation demands has had promising results.